7(x-3)=3x+2

Simple and best practice solution for 7(x-3)=3x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-3)=3x+2 equation:


Simplifying
7(x + -3) = 3x + 2

Reorder the terms:
7(-3 + x) = 3x + 2
(-3 * 7 + x * 7) = 3x + 2
(-21 + 7x) = 3x + 2

Reorder the terms:
-21 + 7x = 2 + 3x

Solving
-21 + 7x = 2 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-21 + 7x + -3x = 2 + 3x + -3x

Combine like terms: 7x + -3x = 4x
-21 + 4x = 2 + 3x + -3x

Combine like terms: 3x + -3x = 0
-21 + 4x = 2 + 0
-21 + 4x = 2

Add '21' to each side of the equation.
-21 + 21 + 4x = 2 + 21

Combine like terms: -21 + 21 = 0
0 + 4x = 2 + 21
4x = 2 + 21

Combine like terms: 2 + 21 = 23
4x = 23

Divide each side by '4'.
x = 5.75

Simplifying
x = 5.75

See similar equations:

| 10x-x=x+4+7x | | 2y+(y+600)=5010 | | Y=-5/3x | | 2x-4x=4+8 | | 1/5x25 | | 8x+4y-2z= | | a^2+17+72= | | 12x+7=18x-23 | | 2x/3=x-15 | | 23=3p-1 | | x^2-6x+9*4x-x*4x-5=0 | | 20(x-5+2)=6 | | 2(y-1)-3=11 | | 2(w-1)/4=2-w | | 8(x+100)+3=837 | | 4xw*5w= | | 8x^2-56x+96=8(x-3)(x-4) | | -6x=42y | | 3g+5(g-2)= | | 64=n-8 | | 15p+16q+p-5q-4p= | | y-5x=-30 | | 6x^2-6xy= | | 3(2x-1)+2x=1-4(x-2) | | 6(1)-2y=6 | | 14a+15b+5c+4c-4b-2a= | | 3d+9e+10d+8e= | | 2x/3=x-5 | | 4/3×-1/2= | | 4/3×-1/2=0 | | 5x+18=3(6-x) | | x=5/(400-20x) |

Equations solver categories